2013
DOI: 10.1007/s11205-013-0452-2
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction and Education in South Africa: Investigating the Role of Attainment and the Likelihood of Education as a Positional Good

Abstract: This paper explores various dynamics in the relationship between life satisfaction and education in South Africa using the 2008 National Income Dynamics Survey. The results indicate a strong positive association between educational attainment and individual satisfaction with life, which is true in the overall sample and for men and women. This positive relationship also holds for Black and Coloured individuals, but is insignificant in the Asian and White samples. Evidence indicates that education is a position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 40 publications
6
29
0
Order By: Relevance
“…The relative argument states that the effect of income or other resources is based on changeable standards typically derived from expectations, social comparisons and habits. Positional status indicates that there is a positive association that can be obtained between life satisfaction and perceived relative income, as supported in the viewpoint in international and South African research (Easterlin, 1995:35-48;2001:465-484;Posel & Casale, 2011:195-223;Botha, 2013). From previous research studies conducted by Diener et al (1985) within countries, a small positive relationship was found between income and SWL.…”
Section: Literature Reviewmentioning
confidence: 64%
“…The relative argument states that the effect of income or other resources is based on changeable standards typically derived from expectations, social comparisons and habits. Positional status indicates that there is a positive association that can be obtained between life satisfaction and perceived relative income, as supported in the viewpoint in international and South African research (Easterlin, 1995:35-48;2001:465-484;Posel & Casale, 2011:195-223;Botha, 2013). From previous research studies conducted by Diener et al (1985) within countries, a small positive relationship was found between income and SWL.…”
Section: Literature Reviewmentioning
confidence: 64%
“…This information is the basis of the dummy variable HighIncome, which is equal to 1 for respondents who rated themselves in income bracket 6 or above in comparison with other Egyptians. Given Perovic's (2010) finding that income has a positive impact on the life satisfaction of Croatians, combined with Botha's (2014) estimates suggesting a similarly positive relationship for South Africans, we expect the value of b 1 to exceed zero.…”
Section: Data and Conceptual Modelmentioning
confidence: 94%
“…Sanfey and Teksoz () find, similarly, that although the more educated experience greater happiness, those living in transition countries are generally less happy than those living in more advanced economies. Lastly, based on data from Croatia, Perovic () finds that higher education, income and wealth have positive impacts on life satisfaction, while Botha (), using a 2008 survey of South Africans, finds that the likelihood of experiencing happiness is positively related to educational attainment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Age is a linear variable while health is measured on a five-point scale, ranging from very bad to very good. Socioeconomic status is crucial in levels of subjective well-being (Antinyan, 2015; Botha, 2014; Calvo et al, 2015). This study controlled for education, occupation, and household income.…”
Section: Methodsmentioning
confidence: 99%